EKSPLORASI TRANSFORMASI DIGITAL DAN INOVASI UMKM ERA EKONOMI DIGITAL DI MALANG RAYA: Inovasi, Transformasi Digital, Ekonomi Digital, UMKM - Kusufa, Fendiyatmi; Tanuwijaya, Sjheny; Sandora, Anggelina (Jurnal Paradigma Ekonomika, 2025)
The purpose of this study is to explore the digital transformation and innovation undertaken by micro, small, and medium enterprises (MSMEs) in the digital economy era, with a particular focus on Batu City, Malang City, and Malang Regency. The current challenges and opportunities for MSMEs in Indonesia amid the rapid development of information and communication technology are the difficulties in adopting digital technology. This study highlights the importance of SMEs in the local economy, particularly in tourist areas such as Batu City, Malang City, and Malang Regency. To enhance competitiveness, operational efficiency, and product innovation, SMEs need to undergo digital transformation. This study aims to identify the digital technologies adopted by SMEs, analyse the impact of their use, and assess the challenges faced during the transformation process. The method used in this study is quantitative. The findings of this study indicate that the higher the level of digital technology adoption by SMEs, the greater the potential for innovation in products, processes, and business models. The application of information technology helps SMEs improve operational efficiency, expand markets, and enhance service quality, directly impacting increased sales and profitability. Through innovation, SMEs can create the added value consumers demand and adapt products to market trends.